Development and cognitive testing of a food-frequency questionnaire to assess intake of plant-based protein foods among older adults - Virginie Drolet-Labelle; Alexandra Bédard; Simone Lemieux; Vicky Drapeau; Lana Vanderlee; Danielle Laurin; Sophie Desroches (Public Health Nutrition)
Abstract